Ab initio study of the cohesive properties, electronic structure and thermodynamic stability of the Ni-In and Ni-Sn intermetallics - Ramos, Susana Beatriz (2013)
A comprehensive study of the structural, cohesive and electronic properties of several stable, metastable and non-stable intermetallic phases (IPs) of the Ni–In and Ni–Sn systems have been performed by ab initio density-funcional-theory (DFT) methods. Using the projector augmented wave method we have performed systematic spin polarized calculations with the exchange and correlation functions of Perdew and Wang in the generalized gradient approximation (GGA), as well as those by Ceperley and Alder in the local-density-approximation (LDA). Structural properties, the energy-of-formation (EOF) from the elements and the cohesive properties of the various phases have been established by minimizing the internal structural parameters. We present trends at 0 K in the composition dependence of the molar volumen, bulk modulus and its pressure derivative, electronic density of states, magnetic moments and the EOF of several stable and metastable IPs reported in the Ni–In and Ni–Sn systems as well as various non-stable (hypothetical) compounds which are relevant in connection with the thermodynamic analysis of the Ni–In and Ni–Sn systems using Gibbs energy models and the so-called CALPHAD techniques. The results are compared with the available experimental data and with previously reported theoretical results. The present study of the thermodynamic and cohesive properties of Ni–In/Sn intermetallic phases should contribute to the understanding of the phase-stability systematics in the Ni–In–Sn system and the design of new soldering alloys.